Demand and supply functions for Irish exports of manufactures - O'Connell, T. (Economic & Social Studies, 1977)
In this paper, we specify and estimate some simple quarterly econometric models of Irish manufactured exports looking at the determinants of both the demand for, and the supply of, manufactured exports. The standard definition of manufactured exports is taken, i.e., SITC (Standard International Trade Classification) 5-8 inclusive; the data period used for estimation is 1964 to 1974 (with extra observations, where necessary, for lags).
Keywords: Irish exports; Manufacturing